The importance of practicing physical activity during Medical graduation (Research, Society and Development, 2023)
Physical activity goes far beyond aesthetics, when we think of students, focusing on medical academic training, we can observe the benefits it provides, such as a better quality of life both in physical and mental aspects and also in academic performance. Medical students, throughout their graduation, go through major changes that interfere with the formation of the individual as a whole, so it is necessary that some activity be present at that time so that the student can release and distract in a healthy way from the innumerable concerns and tasks of the graduation, without the need to use methods such as controlled medications or even licit and illicit drugs to complete this period and end up becoming the patient. That is why the practice of physical activity is so important in this environment, because through it many anxieties, fears and the stress of everyday life can be alleviated, promoting a better quality of life for the student, so that at the end of this process he is a trained professional and especially with health to offer the best care to its patients. Therefore, for this qualitative research, a questionnaire was applied to medical students asking how physical activity influences or not academic life, through questions about daily life and how they feel about practicing or not exercising.